Three Homoclinic Solutions for Second-Order -Laplacian Differential System - Jia Guo; Bin-Xiang Dai (Abstract and Applied Analysis)
We consider second-order -Laplacian differential system. By using three critical points theorem, we establish the new criterion to guarantee that this -Laplacian differential system has at least three homoclinic solutions. An example is presented to illustrate the main result.